Study of the Antimicrobial Activity of Staphylococcal Bacteriophage on a Model of an Infected Skin Wound - G. N. Genatullina (Антибиотики и Химиотерапия, 2024)
The purpose of this study was to investigate the antimicrobial activity of staphylococcal bacteriophage on a model of a skin wound infected with Staphylococcus aureus. The study of antimicrobial activity was carried out in vivo by experimental modeling of a skin wound infected with S.aureus in the interscapular region in nonlinear male rats. All manipulations with animals were performed in accordance with the requirements of regulatory documentation overseeing the management of laboratory animals and work with them. The results obtained indicate the pronounced antimicrobial activity of staphylococcal bacteriophage in conditions of wound infection when applied externally, which is confirmed by a decrease in the degree of bacterial contamination of wound discharge, as well as a decrease in inflammatory phenomena, both at the local level in the form of a decrease in hyperemia, and generalized in the form of a decrease in C-reactive protein levels, total leukocyte count, as well as a decrease in the leukocyte inflammatory index. The identified antimicrobial effect is comparable to the external use of an antiseptic drug — a solution of chlorhexidine digluconate 0.05%, however, when assessing microbial contamination, it was found that the bacteriophage exhibits more pronounced antibacterial activity. Thus, the staphylococcal bacteriophage showed pronounced antimicrobial activity in a model of a skin wound infected with S.aureus, confirmed by a decrease in the number of colonies of the microorganism in the wound discharge, as well as a decrease in the severity of inflammation.